(untitled) (Metallurgy and Foundry Engineering, 2018)
Clinching is an effective joining technique for lightweight sheet materials that are difficult or impossible to weld. Clinching is a relatively new technology in which two to three sheet metal parts are joined together by a process of local plastic deformation without the use of any additional components with the application of a special tool. In this study, an experimental investigation of clinch joints was performed. A non-standardized technique was used to determine the optimal joint geometry for further experiments. The used material type was DP600 (dual-phase, advanced high strength steel).